Thromboprophylaxis for atrial arrhythmias in congenital heart disease: A multicenter study. (15th November 2016) - Khairy, Paul; Aboulhosn, Jamil; Broberg, Craig S.; Cohen, Scott; Cook, Stephen; Dore, Annie; Fernandes, Susan M.; Fournier, Anne; Kay, Joseph; Levesque, Sylvie; Macle, Laurent; Marcotte, François; et al.
Abstract: Background: There is a paucity of data to guide decisions regarding thromboprophylaxis for atrial arrhythmias in congenital heart disease. Methods: A retrospective multicenter cohort study enrolled patients with documented sustained atrial arrhythmias and congenital heart disease from 12 North American centers to quantify thromboembolic and bleeding rates associated with antiplatelet and anticoagulation therapy, and explore associated factors. A blinded committee adjudicated all qualifying arrhythmias and outcomes. Results: A total of 482 patients, 45.2% female, age 32.0 ± 18.0 years, were followed for 11.3 ± 9.4 years since the qualifying arrhythmia. Antiplatelet therapy was administered to 37.8%, anticoagulation to 54.4%, and neither to 7.9%. Congenital heart disease complexity was simple, moderate, and severe in 18.5%, 34.4%, and 47.1%, respectively. Freedom from thromboembolic events was 84.7 ± 2.7% at 15 years, with no difference between anticoagulation versus antiplatelet therapy (P = 0.97). Congenital heart disease complexity was independently associated with thromboembolic events, with rates of 0.00%, 0.93%, and 1.95%/year in those with simple, moderate, and severe forms (P < 0.001). CHADS2 and CHA2 DS2 -VASc scores were not predictive of thromboembolic risk. Annualized bleeding rates with antiplatelet and anticoagulation therapy were 0.66% and 1.82% (P = 0.039). In multivariable analyses, anticoagulation [hazard ratio (HR) 4.76, 95% CI (1.05–21.58), P = 0.043] and HAS-BLED score [HR 3.15, 95% CI (1.02, 9.78), P = 0.047] were independently associated with major bleeds. Conclusion: Current management of atrial arrhythmias in congenital heart disease is associated with a modest rate of thromboembolic events, which is predicted by disease complexity but not CHADS2 /CHA2 DS2 -VASc scores. HAS-BLED score is applicable to the congenital population in predicting major bleeds.